2019
DOI: 10.5114/ceh.2019.88105
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion on explant is associated with presenting tumor characteristics and not direct acting antiviral utilization in hepatitis C candidates undergoing liver transplantation

Abstract: Aim of the study: Utilization of direct acting antiviral (DAA) therapy in candidates with well-compensated hepatitis C virus (HCV) cirrhosis and hepatocellular carcinoma (HCC) accruing end stage liver disease (MELD) exception points is highly variable among transplant centers based on center location, local organ procurement dynamics, HCV(+) organ availability, and patient preference. The association between DAA utilization prior to transplant and incidence of lymphovascular invasion on explant is unknown. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The first retrospective data revealed a significant dropout rate (progression of HCC beyond transplant criteria) in the untreated cohort (6.3%) compared with the DAA‐treated cohort (3.2%) ( P = 0.04) 40 . Moreover, it was also demonstrated that DAA therapy for waitlist active HCV candidates accruing MELD exception points is efficacious with no deleterious effects on bridging LRT or increase of lymphovascular invasion on explants 40 . Moreover, Huang et al 36 .…”
Section: Hepatitis C Virus and Early Hepatocellular Carcinoma—best Timing Of Treatmentmentioning
confidence: 99%
“…The first retrospective data revealed a significant dropout rate (progression of HCC beyond transplant criteria) in the untreated cohort (6.3%) compared with the DAA‐treated cohort (3.2%) ( P = 0.04) 40 . Moreover, it was also demonstrated that DAA therapy for waitlist active HCV candidates accruing MELD exception points is efficacious with no deleterious effects on bridging LRT or increase of lymphovascular invasion on explants 40 . Moreover, Huang et al 36 .…”
Section: Hepatitis C Virus and Early Hepatocellular Carcinoma—best Timing Of Treatmentmentioning
confidence: 99%